What drives the inflow of FDI in OIC countries? Evidence from Top 10 hosts of inward FDI flows - Indri Supriani; Bayu Arie Fianto (Jurnal Ekonomi dan Keuangan Islam, 2020)
Purpose – This study investigates the driven factors of Foreign Direct Investment (FDI) inflow in selected OIC member countries. The selection of samples observation based on the top 10 hosts of inward FDI flows countries, includes the United Arab Emirates (UAE), Morocco, Indonesia, Turkey, Iran, Egypt, Bangladesh, Kazakhstan, Oman, and Malaysia.